THE CHALLENGES OF LAND AND WATER RESOURCES DEGRADATION IN JORDAN : DIAGNOSIS AND SOLUTIONS - Abu-Sharar (Desertification in the Mediterranean Region a Security Issue, 2014)
Desertification is the loss of complexity of biological and/or economic productivity of crop-, range- or wood-lands. Reasons of such a loss is mainly due to climatic change and unsustainable human activities. The arid and semi-arid lands of Jordan are sensitive to human interference that resulted in a severe depletion of its natural resources and in different forms of land degradation due to multiple interaction of socio-economic factors. Further, degradation will continue if human activities are not carefully controlled and managed. Almost 90% of the land area of Jordan receives less than 200 mm of rainfall annually. This is reflected in poor structural stability of soils and the subsequent vulnerability to excessive erosion following shallow rainstorm events. Such a fragile ecosystem has also been manifested by non sustainable land use patterns and poor vegetative cover of the range land and the remaining forest batchs. Therefore, most of the economic activities take place on the remaining 10% of the land area and the competition between different user groups for these lands is, therefore, intense. Factors such as livestock and grazing practices, inappropriate agricultural and irrigation techniques, the marginalizing of lands, poor socio-economic conditions and a high population growth rate as well as weak institutional arrangements need to be considered in a comprehensive and integrated framework. Rangelands are deteriorating at an accelerated rate due to widespread overgrazing, uncontrolled herd movements, firewood collection, unsuitable cultivation practices, and persisted periodic droughts, all of which worsen ecological conditions. Cultivation of marginal lands, and unsound practices such as ploughing down slopes, and use of heavy farm machinery have accelerated rate of soil erosion and lowered land productivity. Urbanisation is also steadily encroaching onto good quality agricultural land in the higher rainfall areas of the Jordanian highlands, reducing the traditional production areas of food crops such as wheat and barley. Jordan suffers from a scarcity of water resources, which is compounded by poor management of existing supplies. Pumping of aquifers for irrigation and municipal uses has been exceeding their renewable safe yield. No serious attempts have been committed to improve natural recharge into these aquifers, encourage water harvesting practices or adopt water conservation measures, especially in irrigation. The current demand for municipal, industrial and agricultural water in Jordan exceeds sustainable water supply and the problem is further aggravated in dry winters like the case in the 1998/99 season. Irrigation has made crop production possible in many areas but the long-term effects of fertilizers and pesticides on water quality, as well as on soil salinity, have been given only limited attention. Furthermore, poor wastewater treatment, and industrial pollution have compounded the problem. Current and future deterioration of water quality will have marked effects on land degradation. Socio-economic factors contribute negatively to desertification and to efforts to combat its effects, poverty constitutes a vicious circle linking deterioration of natural resources to deterioration of livelihoods. Also, the population increase is adding an additional pressure to land and water resources, as people need to encroach further on fragile soils, sparse vegetation and limited water resources. The institutional capabilities of the Government as well as the existing legislation and policies need to address the serious degradation of its agricultural, range and forest lands, and aim to improve land capabilities and increase production for communities will require support. Financial and technical support will be required to introduce new agricultural products, agricultural techniques, water harvesting techniques that will result in increased land productivity, yet with less pressure on fertility and water resources. Also, communities will be encouraged to engage in diversified economic activities that will alleviate pressure on natural resources. This may be accomplished through the adoption of participatory approaches that raise awareness of local communities to threats of desertification and to strengthen local institutions, which are essential for reversing desertification and environmental degradation, especially considering Jordan’s transition economy.
Keywords: Agriculture; degradation; desertification; Jordan; management (voyant); resources; water

Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Using lichen functional diversity to assess the effects of atmospheric ammonia in Mediterranean woodlands - Pinho, Pedro; Dias, Teresa; Cruz, Cristina; Sim Tang, Y; Sutton, Mark A; Martins-Loução, Maria-Amélia; Máguas, Cristina; Branquinho, Cristina (Journal of Applied Ecology, 2011)
1. Atmospheric ammonia (NH3) is one of the main drivers for ecosystem changes world-wide, including biodiversity loss. Modelling its deposition to evaluate its impact on ecosystems has been the focus of many studies. For that, universal indicators are needed to determine and compare the early effects of NH3 across ecosystems. 2. We evaluate the effects of atmospheric NH3 in ecosystems using lichens, which are one of the most sensitive communities at the ecosystem level. Rather than measuring total diversity, we use a functional diversity approach because this is potentially a more universal tool. 3. We evaluated the spatial and temporal patterns of atmospheric NH3 concentrations ([NH3]atm) emitted from a point-source over a 1-year period in a cork oak Mediterranean woodland. We observed a temporal pattern of [NH3]atm, with maximum concentrations during autumn. 4. The distribution of lichen species was c. 90% explained by [NH3]atm. The tolerance of lichen species to atmospheric NH3, based on expert knowledge from literature, was tested for the first time against direct measurements of atmospheric NH3. Most species were well classified, with the exception of Lecanora albella and Chrysothrix candelaris, which were more tolerant than expected. Our updated lichen classification can be used to establish lichen functional groups that respond to atmospheric NH3, and these can be used in other Mediterranean countries. 5. Increasing [NH3]atm led to a complete replacement of oligotrophic by nitrophytic species within 65 m of the NH3 source. The geostatistical analysis of functional diversity variables yielded a spatial model with low non-spatial variance, indicating that these variables can cope robustly with high spatial variation in NH3. 6. Synthesis and applications. Our results support the use of functional diversity variables, such as a lichen diversity value, as accurate and robust indicators of the effects of atmospheric NH3 on ecosystems. The spatial modelling of these indicators can provide information with high spatial resolution about the effects of atmospheric NH3 around point- and diffuse sources. As this methodology is based on functional groups, it can be applied to monitor both the impact of atmospheric NH3 and the success of mitigation strategies.
Keywords: Agriculture; atmospheric NH3; biodiversity loss; Cattle; Ecological indicators; Global change; spatial analysis

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology